Sports injuries in young soccer players: prevalence and associated factors - Elaine Gimenes Nunes, Heloyse (2021)
Introduction: Soccer is the most performed sport modality in the world with thousands of practitioners, including children and teenagers. Objective: To analyze the occurrence of sports injuries (SIs) and its relationship with associated factors to SIs in young soccer players. Methods: The sample comprised 102 players (aged 12 to 18 years old) from two soccer clubs. Information on training and anthropometry was recorded, and SIs data were obtained by means of a referred morbidity survey. Considering the rate of SIs per participant (2.4 SIs/ individual), two groups were established: Group 1 (G1, n=61), composed of volunteers with a history of up to two cases of SIs, and Group 2 (G2, n=41), with participants with at least three cases of SIs. Student t and Fisher tests were used to compare groups; SI occurrences were analyzed by descriptive methods. Binary logistic regression was employed to evaluate the relationship among associated factors and SI occurrences in young soccer players. Results: A total of 245 cases of SIs were reported by 81 volunteers (79.4%). Contact was the main cause of musculoskeletal injuries (56.8%); 74.4% of SI included lower limbs. Body composition and exposure were directly associated with SIs recurrence. G2 presented higher body weight (G1, 56.7±9.5; G2, 61.6±12.5kg) and sport practice (G1, 4.8±2.6; G2, 6.2±2.7 years) than G1. Conclusion: Most LEs had lower limb installment due to trauma. The higher the body mass index and exposure to training, the greater the chance of presenting three or more injuries.